An innovative passive sampler to reveal the high contribution of biomass burning to black carbon over Indo-China Peninsula: Radiocarbon constraints. (1st February 2023) - Wang, Xiao; Li, Jun; Zhang, Xiangyun; Cheng, Zhineng; Jiang, Haoyu; Jiang, Hongxing; Lin, Boji; Zhu, Sanyuan; Zhao, Shizhen; Liu, Junwen; Tian, Chongguo; Zhang, Ruijie; et al.
Abstract: Black carbon (BC) is an important component of the brown clouds, contributing to climate and health effects of air pollution. In this work, we developed a new method for measuring BC concentrations and its radiocarbon isotope ( 14 C) using quartz wool disk passive air samplers (Pas-QW). A field calibration study was conducted at two sampling sites (Guangzhou and Yantai), using an improved thermal/optical method to measure BC. Uptake profiles of Pas-QW were linear over the 77 days that the samplers were deployed, and the average sampling rate of BC measured was 1.1 ± 0.2 m 3 /day. The method was found to be reproducible with coefficients of variation as low as 17% for BC measured in ambient passive samples. Furthermore, passive sampling was carried out at six sites in the Indo-China Peninsula (ICP) from January to April and June to September of 2016. The high BC concentrations and the high fraction of modern carbon ( f M ) values emphasizes that ICP is still dominated by biomass burning emissions (residential cooking and agricultural burning), both in dry and wet seasons. This study provides a proof concept and methodology for the application of Pas-QW to cost-effectively expand measurements of BC at the global scale. Graphical abstract: Image 1 Highlights: A new method for measuring BC and its 14 C using quartz wool disk passive samplers. The method requires no sample processing and have good reproducibility for BC. The relative contribution of biomass burning to BC can reach 67 ± 13% in ICP, with obvious spatiotemporal heterogeneity.